Metabolic engineering of Corynebacterium glutamicum for de novo production of 3-hydroxycadaverine - Carina Prell; Sophie-Ann Vonderbank; Florian Meyer; Fernando Pérez-García; Volker F. Wendisch (Current Research in Biotechnology, 2022)
Functionalization of amino acids and their derivatives opens up the possibility to produce novel compounds with additional functional groups, which can expand their application spectra. Hydroxylation of polyamide building blocks might allow crosslinking between the molecular chains by esterification. Consequently, this can alter the functional properties of the resulting polymers. C. glutamicum represents a well-known industrial workhorse and has been used extensively to produce lysine and lysine derivatives. These are used as building blocks for chemical and pharmaceutical applications. In this study, it was shown for the first time that C3-hydroxylated cadaverine can be produced de novo by a lysine overproducing C. glutamicum strain. The lysine hydroxylase from Flavobacterium johnsoniae is highly specific for its natural substrate lysine and, therefore, hydroxylation of lysine precedes decarboxylation of 4-hydroxylysine (4-HL) to 3-hydroxycadaverine (3-HC). For optimal precursor supply, various cultivation parameters were investigated identifying the iron concentration and pH as major effectors on 4-HL production, whereas the supply with the cosubstrate 2-oxoglutarate (2-OG) was sufficient. Deletion of the gene coding for the lysine exporter LysE suggested that the exporter may also be involved in the export of the structurally similar 4-HL. With the optimised setting for 4-HL production, the pathway was extended towards 3-HC by decarboxylation. Three different genes coding for lysine/4-HL decarboxylases, LdcC and CadA from E. coli and DCFj from F. johnsoniae, were expressed in the 4-HL producing strain and compared regarding 3-HC production. It was shown in a semi-preparative biocatalysis that all three decarboxylases can accept 4-HL as substrate with varying efficiencies. In vivo, LdcC supported 3-HC production best with a final titer of 11 mM. To improve titers a fed-batch cultivation in 1 L bioreactor scale was performed and the plasmid-based overexpression of ldcC was induced after 24 h resulting in the highest titer of 8.6 g L-1 (74 mM) of 3-hydroxycadaverine reported up to now.